Pengaruh Model Creative Problem Solving dengan Etnosains Terhadap Kemampuan Pemecahan Masalah dan Sikap Ilmiah Siswa - Rifki Nomizar Khairani; A.K. Prodjosantoso (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to analyze whether there are significant differences in problem-solving abilities and scientific attitudes between students who use the ethnoscience-based creative problem-solving learning model and students who use the Discovery learning model on colloidal materials. This research was conducted at SMA N 6 Yogyakarta and SMA N 11 Yogyakarta using a quasi-experimental method with data analysis techniques using MANOVA. Data collection techniques in this research are observation, interviews, questionnaires, and tests. The results showed that there were significant differences in problem-solving abilities and scientific attitudes between experimental class and control class students, with a significance of 0.00 < 0.05 and an effective contribution of 13.6% in the moderate category. Therefore, it can be concluded that the use of a creative problem-solving learning model based on ethnoscience has a significant influence on improving students' chemical problem-solving abilities and scientific attitudes towards colloidal materials.